Effectiveness of multicomponent interventions in primary healthcare settings to promote continuous smoking cessation in adults: a systematic review - Carlos Martín Cantera; Elisa Puigdomènech; Jose Luis Ballvé; Olga Lucía Arias; Lourdes Clemente; Ramon Casas; Lydia Roig; Santiago Pérez-Tortosa; Laura Díaz-Gete; Sílvia Granollers (BMJ Open)
Objective The objective of the present review is to evaluate multicomponent/complex primary care (PC) interventions for their effectiveness in continuous smoking abstinence by adult smokers.Design A systematic review of randomised and non-randomised controlled trials was undertaken.Eligibility criteria for included studies Selected studies met the following criteria: evaluated effects of a multicomponent/complex intervention (with 2 or more intervention components) in achieving at least 6-month abstinence in adult smokers who visited a PC, biochemical confirmation of abstinence, intention-to-treat analysis and results published in English/Spanish.Methods We followed PRISMA statement to report the review. We searched the following data sources: MEDLINE, Web of Science, Scopus (from inception to February 2014), 3 key journals and a tobacco research bulletin. The Scottish Intercollegiate Guidelines Network checklists were used to evaluate methodological quality. Data selection, evaluation and extraction were done independently, using a paired review approach. Owing to the heterogeneity of interventions in the studies included, a meta-analysis was not conducted.Results Of 1147 references identified, 9 studies were selected (10 204 participants, up to 48 months of follow-up, acceptable methodological quality). Methodologies used were mainly individual or group sessions, telephone conversations, brochures or quit-smoking kits, medications and economic incentives for doctors and no-cost medications for smokers. Complex interventions achieved long-term continuous abstinence ranging from 7% to 40%. Behavioural interventions were effective and had a dose–response effect. Both nicotine replacement and bupropion therapy were safe and effective, with no observed differences.Conclusions Multicomponent/complex interventions in PC are effective and safe, appearing to achieve greater long-term continuous smoking cessation than usual care and counselling alone. Selected studies were heterogeneous and some had significant losses to follow-up. Our results show that smoking interventions should include more than one component and a strong follow-up of the patient to maximise results.